Taking stock an update on child surviv al & development in Uganda - UNICEF Uganda (Kampala : UNICEF Uganda, 2007)
This CD provides a historical perspective, an update of the situatio n of women and children in Uganda and selected priority programmatic fo cus for UNICEF Uagnda over the next three years
Systems requirements: Macromedia flash player
Keywords: Child welfare -- Uganda; Children -- Mortality -- Uganda; Child development -- Uganda